(3CdajI GdYQGbj aj CUhd GdMOjKs - (3GdYQGbj, Rjf GdOjf, YHO GdQMef Hf GdMSjf, J (B806(3g`s ((3eOQSI GdefbGQj HeOjfI JhbGJs)
(3ChdgG (B:s
(3HYO GdHSedI ; jbhd QGLj QHg GdebJOQ YHO GdQMje Hf GdMSjf GdCKQj (B- (3ef HYO MeO Gddg Pj GdBdGA Ydi GeJfGf Ld Yf GMUGAs
(3BNQgG (B:s
(3aQHfG GdeMehO hGdeTchQ Edjg efG JQLY GdCehQ (B- (3hCaVd GdUdhI hGdSdGe Ydi GdfHj SjO GdCfGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 344s
(3eYLe GdeDdajf (B2 / 130s
(3cTa GdXfhf (B1/ 156s
(3TPQGJ GdPgH (B7 / 55s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs